Molten Oxide Electrolysis Using Copper-Containing Carbon-Saturated Molten Iron Anode. Issue 2 (1st February 2023) - Natsui, Shungo; Sato, Takahiro; Ito, Akihisa; Hayasaka, Miho; Iwama, Takayuki; Mori, Kota; Ueda, Shigeru; Nogami, Hiroshi
Abstract : This study focused on the use of molten oxide electrolysis (MOE) as a low-cost, clean, continuous separation method suitable for incorporation into actual steelmaking processes. We discussed interfacial behavior from molten iron to slag by anodic polarization of the copper-containing carbon-saturated molten iron (metal phase)–molten oxide (slag phase) interface and investigate the operating mechanism of MOE. The basic constant potential electrolysis between the metal phase (Fe-10 wt% Cu-5.0 wt% C) and slag phase (27 wt% CaO-27 wt% SiO2 −45 wt% Al2 O3 −1.0 wt% CaS) by maintaining 1–2 V vs Pt at 1773 K in an Ar atmosphere is described. When polarized, a high concentration of dispersed Cu-rich phase was detected locally near the metal–slag interface but not in the phase center of the metal. At the metal–slag interface, the energies of the Fe-rich and Cu-rich phase–slag interfaces decreased due to electric capillarity, and the Cu-rich phase distributed near the interface.